2021
DOI: 10.1161/jaha.121.022747
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heme Oxygenase‐1 Is Linked to the Severity of Disease in Human Abdominal Aortic Aneurysm

Abstract: Background Rupture of abdominal aortic aneurysm (rAAA) is associated with high case fatality rates, and risk of rupture increases with the AAA diameter. Heme oxygenase‐1 (gene HMOX1 , protein HO‐1) is a stress‐induced protein and induction has protective effects in the vessel wall. HMOX1 −/− mice are more susceptible to angiotensin II‐induced AAA formation, but the regulation in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Emerging evidence has suggested that the development of AAAs in humans is related to vascular oxidative stress and inflammation [ 23 , 40 , 41 , 42 , 43 ]. Therefore, reducing oxidative stress and inflammation can be an efficient strategy for limiting AAA development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested that the development of AAAs in humans is related to vascular oxidative stress and inflammation [ 23 , 40 , 41 , 42 , 43 ]. Therefore, reducing oxidative stress and inflammation can be an efficient strategy for limiting AAA development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, aortic HO-1 mRNA and protein expressions in response to prescription of lipid-lowering and antihypertensive therapies as well as therapeutic anticoagulation were analyzed in aortic tissues of patients with late-stage AAA. These therapies were tested for their potential to induce HO-1 expression because an induction of HO-1 is considered to be protective in many cardiovascular diseases, including AAA [ 10 , 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription of mRNA into cDNA was performed with MultiScribe reverse transcriptase (Thermo Fisher Scientific, Darmstadt, Germany) using random hexamer primers according to the manufacturer’s instructions. Quantification of mRNA expression was performed by real-time PCR with GoTaq qPCR master mix (Promega, Walldorf, Germany) and the Step One Plus Real-Time PCR system (Thermo Fisher Scientific, Darmstadt, Germany) [ 13 ]. A geometric mean of three reference genes, namely, ribosomal protein L32 ( RPL32 ), TATA-box binding protein ( TBP ), and beta-2-microglobulin ( B2M ), was used for cDNA content normalization [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations